P.109: Improvement of the Outcoupling Efficiency of Blue OLEDs. Issue 1 (1st July 2013) - Kim, Dong‐Young; Choi, Chung Sock; Lee, Sung‐Min; Choi, Kyung Cheol; Chae, Gee Sung; Joo, Sung Hoon; Park, Jung Soo; Yang, Joong Hwan
Abstract: We propose a nanostructured blue organic light‐emitting diode (OLED) with a perforated WO3 hole injection layer that improves the outcoupling efficiency of blue OLEDs by the extraction of trapped surface plasmon polaritons and wave guide modes.